Query acceleration in distributed database systems - Haraty, Ramzi A. (2001)
The advent of telecommunication era and the constant development of hardware and network structures have encouraged the decentralization of data while increasing the needs to access information from different sites. Query optimization strategies aim to minimize the cost of transferring data across networks. Many techniques and algorithms have been proposed to optimize queries. Perhaps one of the more important algorithms is the AHY algorithm using semi-joins that is implemented by Apers, Hevner and Yao in [1]. Nowadays, a new technique called PERF (Partially Encoded Record Filters) seems to bring some improvement over semi-joins [12]. PERF joins are two-way semi-joins using a bit vector as their backward phase. Our research encompasses applying PERF joins to two well know algorithms: AHY and W, which both deal with query optimization. Programs were designed to implement both the original and the enhanced algorithms. Several experiments were conducted and the results showed a very considerable enhancement obtained by applying the PERF concept. This major improvement led us to further observations and studies.